Make it all about them : winning sales presentations - Keller, Nadine, 1962- (Hoboken, N.J. : Wiley, 2013)
'In today's commodity-based marketplace it is harder than ever to differentiate even the most superlative services and products. The sales presentation provides the most powerful opportunity to do so. Make It All About Them reveals the truth behind the traditional rules of presentations and offers sales professionals a new way forward. It explains why focusing on three key points trumps a presentation full of details, why plain English always wins over jargon, why the audience doesn't need to know how important you are but how important they are, and other effective tactics.'--Publisher's website.
Make it all about them -- Start with the end in mind -- Develop a story -- Developing stories for existing clients (rebids) -- Facilitating the experience -- Speaking the client's language -- Making it compelling -- Anticipating and answering questions -- Behaving as a team: team dynamics -- Analyzing your audience -- Dodging the bullets: avoiding death by PowerPoint -- The strategy behind the materials.
Includes index.
Keywords: Sales presentations; Business presentations